Effects of Participatory Design Planning in Public Service Delivery on Students’ Skills in the Innovation in Public Governance and Administration Course, Master of Public Administration Program, A Private University - Whangmahaporn, Piyakorn (Dhammathas Academic Journal, 2026)
This research aimed to: 1) examine students’ analytical thinking and creative thinking skills before and after the implementation of a public service participation plan; 2) evaluate the effects of the public service participation plan on the development of students’ teamwork and communication skills; and 3) investigate recommendations regarding the design and implementation of the public service participation plan. A mixed-methods research design was employed. For the quantitative phase, data were collected from 80 Master of Public Administration students enrolled in the Public Governance and Administration course during the 2024 academic year. A questionnaire was used as the research instrument. Data were analyzed using mean, standard deviation, and paired-samples t-test. For the qualitative phase, data were collected from 30 key informants through observation and in-depth interviews and were analyzed using content analysis. The findings revealed that: after participating in activities based on the public service participation plan, students demonstrated significantly higher levels of analytical thinking and creative thinking skills than before participation at the .05 level of statistical significance. The mean score for analytical thinking increased from 3.061 to 4.441 (t = -15.660), while the mean score for creative thinking increased from 2.672 to 4.813 (t = -17.315). In addition, students showed improvement in teamwork and communication skills. They were better able to exchange ideas, collaborate with others, and communicate more effectively. Furthermore, participants provided recommendations for improving the design and implementation of the participation plan to enhance learning effectiveness. The study concludes that the public service participation plan is an effective learning tool for promoting students’ thinking skills, collaborative skills, and self-directed learning. The findings are consistent with Buddhist principles emphasizing mutual support in collaborative work and rational thinking, which can be appropriately applied to the development of learning processes in the field of public administration.